The Influence of Hedonic Value, Utilitarian Value, and Economic Value on Ride-Hailing App Users in Indonesia in a Sustainable Way - Bayu Erik Prasetyo (Jurnal Indonesia Sosial Teknologi, 2024)
The transportation industry has undergone significant changes due to technological developments and increasing consumer demand for efficiency. In Indonesia, the emergence of ride-hailing apps such as Go-Jek, Grab, and Maxim reflects a growing preference for the sharing economy model. This study aims to analyze the influence of hedonistic values, utilitarian values, and economic values on consumer satisfaction, as well as the influence of satisfaction on the intention to continue using this application. Data was collected from 210 active users through an online survey. The results showed that hedonistic value and economic value had a significant positive impact on user satisfaction, while utilitarian value had no effect. In addition, economic value and satisfaction have a positive effect on the intention to continue using ride-hailing services. In conclusion, to increase user loyalty, ride-hailing service providers need to prioritize increasing economic value and user satisfaction. This study provides insights into the development of services that are more in line with consumer needs and preferences in the digital era.